Quality of life in chronic low back pain patients from orthopedic disease. - Lertthongthai, C.; Nimnuan , C. (Chulalongkorn Medical Journal, 2023)
Background : Chronic low back pain (CLBP) is a public health problem that is most prevalent in working age group and the elderly; it impairs daily activities or work functions that results in poor quality of life leading to emotional and mental disorders. Objective : To study the quality of life of CLBP patients from orthopedic disease. Design : A cross - sectional descriptive study. Setting : Department of Orthopedic and the Department of Physical Medicine and Rehabilitation of King Chulalongkorn Memorial Hospital. Materials and Methods : Data were collected from 290 CLBP patients using demographic data questionnaire, general health and related symptoms of low back pain data questionnaire and World Health Organization Quality of Life Brief – Thai (WHOQOL-BREF-THAI).Descriptive statistics were used to analyze data Independent – Samples t-test and One – Way ANOVA were used to examine association between factors and quality of life. Multiple linear regression analysis was used to determine the predictors of quality of life among CLBP patients. Results : Ninety-three percent had average level of quality of life (QOL). The higher the number of dysfunction, the lower is the level of QOL (B=-2.199, p<.001, 95% CI=-3.183 to -1.214). Men had higher QOL than women (B = -2.818, p=0.002, 95% CI = -4.612 to -1.024). Well-off group had higher QOL than those of lower economic status (B =-5.322, p = 0.008, 95% CI = -9.219 to -1.426). Those with no underlying disease had higher QOL than those with underlying disease (B = -2.461, p = 0.014, 95% CI = -4.419 to - 0.503). Those with lower pain score (0 - 5) had higher QOL these with high pain score (6 - 10), but with no statistical significance (B = -1.137, p = 0.190, 95% CI = -2.843 to 0.568). Conclusion : Most CLBP patients had good quality of life. Therefore, to determining and improving factors that are related to QOL can increase the level of QOL of the patients.